Assessing the relationship between market orientation and business performance in the hotel industry: the mediating role of service quality - Sampaio, Carlos (2018)
This is the accepted manuscript of an article published by Emerald Publishing Limited in Journal of Knowledge Management in 2018, available online: https://www.emeraldinsight.com/doi/abs/10.1108/JKM-08-2017-0363